Soluble CD36 Concentration in Diabetic Hypertensive Patients with Coronary Atherosclerosis - Khaleel, Amer Ali; Al-Barzinji, Ruqaya Mohammed Ghareeb Taher (Cellular and Molecular Biology, 2022)
Atherosclerosis is a chronic condition defined by cholesterol retention and arterial wall inflammation. CD36 is indeed a membrane protein found in the monocyte-macrophage systems and endothelial cells involved in the cellular uptake of oxidized low-density lipoproteins and long-chain fatty acids with a crucial role in the pathophysiology of atherosclerosis. The purpose of this research is to compare the diagnostic usefulness of soluble CD36 (sCD36) to high sensitivity C reactive protein (hs-CRP) in diabetic hypertensive individuals with coronary atherosclerosis and the correlation between these parameters in research groups. One hundred individuals with coronary atherosclerosis were divided into four groups based on diabetes mellitus (DM) and/or hypertension (HTN), with 100 participants with routine angiography serving as a control group. The serum levels of sCD36 and hs-CRP were quantified using a sandwich enzyme-linked immunosorbent assay (ELISA) for sCD36 and a particle-enhanced immune turbidimetric assay for hs-CRP, respectively. A study group's lipid profiles, hematological markers, and clinical aspects were compared. Compared to the control, sCD36 and hs-CRP levels in patients increased considerably (p<0.05). The sCD36 level varied substantially between groups (p<0.05), with the DM-HTN group having the highest sCD36 level among the patient groups. Further, the hs-CRP level indicated a significant difference among patients and controls (p<0.05). CD36 correlated significantly and positively with the following terms BMI, hs-CRP, Total cholesterol and non-HDL-C (p<0.05).